2005
DOI: 10.1111/j.1945-5100.2005.tb00424.x
|View full text |Cite
|
Sign up to set email alerts
|

The Zakłodzie enstatite meteorite: Mineralogy, petrology, origin, and classification

Abstract: Abstract-The Zak≥odzie meteorite was found in September 1998, about 40 km west of ZamoúÊ, in southeast Poland. Macroscopic and microscopic observations (in transmitted and reflected light), microprobe analyses, cathodoluminescence images, and X-ray diffraction data show that the meteorite is composed of clino-and orthoenstatite, two generations of feldspars, relict olivine (forsterite), a polymorph of SiO 2 (apparently cristobalite), and opaque minerals: Fe-Ni alloy (kamacite and taenite), troilite, schreibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…After partial melting and annealing, NWA 2526 experienced a second, relatively mild impact event (<~20 GPa) that caused formation of the polysynthetic twinning in the enstatite. We suggest that the meteorite Zak≥odzie, which has been referred to as a "primitive enstatite achondrite" (Przylibski et al 2005), did not form from a magma of internal origin, but that it is an impact-melt breccia of enstatite chondrite-like parentage, as previously discussed by Burbine et al (2000) and Keil (2007).…”
supporting
confidence: 64%
See 3 more Smart Citations
“…After partial melting and annealing, NWA 2526 experienced a second, relatively mild impact event (<~20 GPa) that caused formation of the polysynthetic twinning in the enstatite. We suggest that the meteorite Zak≥odzie, which has been referred to as a "primitive enstatite achondrite" (Przylibski et al 2005), did not form from a magma of internal origin, but that it is an impact-melt breccia of enstatite chondrite-like parentage, as previously discussed by Burbine et al (2000) and Keil (2007).…”
supporting
confidence: 64%
“…Specifically, Keil (2007) noted that the relict chondrule shown in Fig. 2 in Przylibski et al (2005) and identified as such by these authors is a common feature of impact-melt breccias of enstatite chondrite parentage (e.g., . Keil (2007) also noted that the euhedral enstatite laths surrounded by metallic Fe,Ni are typical for enstatite chondrite impact-melt rocks and breccias and are indicators of impact melting followed by relatively fast cooling (e.g., .…”
Section: Comparison Of Nwa 2526 To Other Unusual Enstatite Meteoritesmentioning
confidence: 97%
See 2 more Smart Citations
“…There are some differences in results obtained using Mössbauer spectroscopy [1] and other methods [2,3]. The biggest difference is relatively small amount of metal (FeNi) in Mössbauer spectrum comparing to other techniques.…”
Section: Sample "2003"mentioning
confidence: 98%